Meta-Analysis: The Effect of PhET Simulation Media on Enhancing Conceptual Understanding in Physics Learning - Khofifah Khofifah; Hadma Yuliani; Santiani Santiani (Jurnal Ilmiah Pendidikan Fisika, 2023)
In the learning process, using interesting media can improve the quality of learning, especially in understanding concepts. PhET simulation media is one of the learning media that can be used. This research is one type of research to know how high the effect of learning by using PhET simulation media using meta-analysis to improve understanding of concepts in physics learning is. Meta-analysis, used as a research method, consists of formulating problems, collecting, coding, analyzing, and interpreting data. The population and sample were used as research material in scientific articles published nationally discussing the effect of PhET simulation media to improve understanding of concepts in physics learning in 2017–2022. Based on the research conducted, an effect size value of 1.48 was obtained, and the interpretation of the effect size value of the effect of PhET simulation media with the dependent variable, namely understanding of concepts in physics learning, was 92% so that the research conducted was classified in the high category. This means that the PhET simulation media have a strong effect on increasing the effectiveness of students' understanding of concepts in physics learning, especially at the SMA, SMK, or MA education level. Thus, PhET is one of the learning media in the form of interactive simulations that can be utilized in education because it presents complex data about processes and concepts so that students can more easily understand the subjects taught in detail.